2008
DOI: 10.1158/1078-0432.ccr-07-1243
|View full text |Cite
|
Sign up to set email alerts
|

Using Pharmacokinetic and Pharmacodynamic Modeling and Simulation to Evaluate Importance of Schedule in Topotecan Therapy for Pediatric Neuroblastoma

Abstract: Purpose: The study aims to use mathematical modeling and simulation to assess the relative contribution of topotecan systemic exposure and scheduling in the activity and myelosuppression of topotecan in pediatric patients with neuroblastoma. Experimental Design: Pharmacokinetic and pharmacodynamic data were obtained from a phase II study for pediatric patients with high-risk neuroblastoma. The topotecan dosage was individualized to attain a topotecan lactone area under the plasma concentration-time curve betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 31 publications
(45 reference statements)
2
48
0
Order By: Relevance
“…Several pharmacokinetic (PK)/pharmacodynamic models have been published over the last decade describing myelosuppression response occurring during cancer treatment with chemotherapy agents (Minami et al, 1998;Zamboni et al, 2001;Friberg et al, 2002;Krzyzanski and Jusko, 2002;Panetta et al, 2003Panetta et al, , 2008. The most used and accepted model was developed by Friberg et al (2002), hereafter the reference model, which has demonstrated consistency among a wide variety of anticancer agents (Latz et al, 2006;Fetterly et al, 2008;Soto et al, 2010b) and has been used to describe neutropenic effects after drug combinations (Sandstrom et al, 2005;Soto et al, 2010a) and predict human hematologic toxicity from laboratory animal data (Friberg et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several pharmacokinetic (PK)/pharmacodynamic models have been published over the last decade describing myelosuppression response occurring during cancer treatment with chemotherapy agents (Minami et al, 1998;Zamboni et al, 2001;Friberg et al, 2002;Krzyzanski and Jusko, 2002;Panetta et al, 2003Panetta et al, , 2008. The most used and accepted model was developed by Friberg et al (2002), hereafter the reference model, which has demonstrated consistency among a wide variety of anticancer agents (Latz et al, 2006;Fetterly et al, 2008;Soto et al, 2010b) and has been used to describe neutropenic effects after drug combinations (Sandstrom et al, 2005;Soto et al, 2010a) and predict human hematologic toxicity from laboratory animal data (Friberg et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few mathematical models of metronomic therapy have been published, none of which accounts for interactions among cancer cells, CSCs, immune cells, and tumor blood vessels (26)(27)(28)(29)(30)(31)(32). To this end, we have developed a mathematical model for tumor growth that accounts for three different phenotypes of cancer cells-nonstem cancer cells (CCs), CSCs (which are more resistant to drugs, hypoxia, and the immune system), and CCs that are induced by chemotherapy to acquire a more stem-like phenotype, which we refer to as treatment-induced cancer cells (ICCs) (33), as well as immune cells [natural killer (NK) cells, CD8 + T cells, and Tregs], tumor vasculature, and their interactions (Fig.…”
mentioning
confidence: 99%
“…2A). The model is based on established pharmacodynamics and known effects of each of the agents [21][22][23][24][25][26][27][28][29] on the cell cycle for 10 tumor types [31][32][33][34][35][36][37][38] and for erythroblasts 39 (erythroblasts have the highest proliferative index of marrow (Fig. 2B).…”
Section: Drug Selectionmentioning
confidence: 99%
“…f(t) is a probability of effect based on the individual [16][17][18][19][20] or combined [21][22][23][24][25][26][27][28][29] effects of temsirolimus, topotecan, and bortezomib which have been previously described.…”
Section: Monitoring and Treatment Assessmentmentioning
confidence: 99%